Discrete crack dynamics: A planar model of crack propagation and crack-inclusion interactions in brittle materials. (November 2018) - Ebrahimi, M.T.; Dini, D.; Balint, D.S.; Sutton, A.P.; Ozbayraktar, S.
Abstract: The Multipole Method (MPM) is used to simulate the many-body self-consistent problem of interacting elliptical micro-cracks and inclusions in single crystals. A criterion is employed to determine the crack propagation path based on the stress distribution; the evolution of individual micro-cracks and their interactions with existing cracks and inclusions is then predicted using what we coin the Discrete Crack Dynamics (DCD) method. DCD is fast (semi-analytical) and particularly suitable for the simulation of evolving low-speed crack networks in brittle or quasi-brittle materials. The method is validated against finite element analysis predictions and previously published experimental data.